Strategi Penyelesaian Konflik Dan Penguatan Tata Kelola Organisasi Masyarakat (Ormas) Di Kabupaten Bojonegoro : Studi Magang Di Bakesbangpol - Maharani Azi Sandra Z.P; Caranoya Ramadhanti S (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the dynamics of inter-community organization (ormas) conflicts and collaborative ormas management strategies in Bojonegoro Regency. Using a qualitative approach and the author’s direct participation during an internship at Bakesbangpol Bojonegoro (13 January -7 March 2025), data were collected through in-depth interviews, participatory observation, and policy document analysis. The results indicate that ormas conflicts in Bojonegoro in 2025 were dominated by economic competition, such as disputes over parking areas and local infrastructure projects. Bakesbangpol acted as a mediator by implementing local wisdom-based conflict resolution models, including traditional deliberation and inclusive economic approaches. A key finding is the successful transformation of “Pemuda Mandiri” (Ormas X) and “Gerakan Bojonegoro Bersatu” (Ormas Y) from conflict groups into development partners through MSME empowerment programs. Meanwhile, “Laskar Hijau” (Ormas Z) exemplifies successful community-based environmental management. This study concludes that synergy between cultural approaches, policy transparency, and economic empowerment is key to reducing ormas conflicts.